What is the best housing temperature to translate mouse experiments to humans? - Jaap Keijer; Min Li; John R. Speakman (Elsevier, 2019)
Objectives: Ambient temperature impinges on energy metabolism in a body size dependent manner. This has implications for the housing temperature at which mice are best compared to humans. In 2013, we suggested that, for comparative studies, solitary mice are best housed at 23-25 °C, because this is 3-5 °C below the mouse thermoneutral zone and humans routinely live 3-5 °C below thermoneutrality, and because this generates a ratio of DEE to BMR of 1.6-1.9, mimicking the ratio found in free-living humans. Methods: Recently, Fischer et al. (2017) challenged this estimate. By studying mice at 21 °C and at 30 °C (but notably not at 23-25 °C) they concluded that 30 °C is the optimal housing temperature. Here, we measured energy metabolism of C57BL/6 mice over a range of temperatures, between 21.4 °C and 30.2 °C. Results: We observed a ratio of DEE to BMR of 1.7 at 27.6 °C and of 1.8 at 25.5 °C, suggesting that this is the best temperature range for housing C57BL/6 mice to mimic human thermal relations. We used a 24 min average to calculate the ratio, similar to that used in human studies, while the ratio calculated by Fisher et al. dependent on short, transient metabolic declines. Conclusion: We concur with Fisher et al. and others that 21 °C is too cool, but we continue to suggest that 30 °C is too warm. We support this with other data. Finally, to mimic living environments of all humans, and not just those in controlled Western environments, mouse experimentation at various temperatures is likely required. Keywords: Housing temperature, Thermoneutrality, Comparative physiology, Basal metabolic rate, Human, Mouse